Cardiac Disease and HIV in Africa: A Case for Physical Exercise - Mocumbi, Ana Olga (Open AIDS J, 2015)
AIDS-related deaths and new HIV infections have declined globally, but continue to be a major problem in Africa. Prior to the advent of antiretroviral treatment (ART) HIV patients died of immunodeficiency and associated opportunistic infections; Highly Active Antiretroviral Therapy (HAART) has resulted in increased survival of these patients and has transformed this illness into a chronic condition. Cardiovascular, respiratory, neurological and muscular problems interfere with exercise in HIV-infected patients. Particularly cardiovascular disease may be associated with direct damage by the virus, by antiretroviral therapy and by malnutrition and chronic lung disease, resulting in physical and psychological impairment. Recent studies have shown the benefits of exercise training to improvement of physiologic and functional parameters, with the gains being specific to the type of exercise performed. Exercise should be recommended to all HIV patients as an effective prevention and treatment for metabolic and cardiovascular syndromes associated with HIV and HAART exposure in sub-Saharan Africa.